The role of information and memory in shaping organisational improvisation - Arshad, Darwina; Lamsali, Hendrik (2012)
Improvisation has recently emerged in managerial studies as a crucial element for organisations to survive.In the mean time, the role of information and memory within the organisation is also imperative in order to achieve improvisational actions.This study proposesan examination on the potential link between organisational improvisation and information and memory.Specifically the aim of this study is to identify the effect of organisational information and memory on organizational improvisation.Two hypotheses are put forward in order to achieve the aforementioned research goal.The research is expected to be beneficial to both relevant practitioners and theorists in the field of business management.